PURWARUPA PINTU GESER RAHASIA MENGGUNAKAN ARDUINO - , MIFTAKHUS S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowdays, the development of increasingly advanced technology along with increasing time. One of the benefits of the technology itself is secure valuables such as jewelry, electronic equipment, securities, etc.. So it needs a secret room to accommodate the items in the room that if it is worth it. In this study has made a prototype room which has a sliding door and 2 proximity sensor (ultrasonic sensor) is used as a trigger to unlock and lock the door of the room. Ultrasonic sensor is a sensor that works by emitting a wave and then calculate the wave reflection time. When the sensor is in a state logic True, then the sensor will send commands to the Arduino which will be processed for the solenoid activates the door lock. Communication between users by using hand tools as its interface. The results show that the secret sliding door system successfully created and can work well as expected.